P549 Should children with down syndrome receive prophylactic antibiotics to prevent recurrent respiratory infections?. (June 2019) - Chia, Evan; Clark, Allison; Flynn, Breanna; Kenna, Michael Mc; Ng, Nyin Nyee; Sherry, Sophie; Stacey, Dylan; Tey, Zhong Hern; Allen, John; Lagan, Niamh; Meehan, Judith; Molloy, Eleanor
Abstract : Introduction: Trisomy 21, also known as Down syndrome (DS), is a clinical disorder where a third copy of chromosome 21 is present. Approximately 95% of DS are due to a meiotic nondisjunction, with the remaining 5% caused by chromosomal translocation or mosaicism. Children with DS are predisposed to recurrent respiratory infections due to a number of anatomical and immunological features. Our project investigated whether there is evidence supporting or refuting the use of antibiotic prophylaxis for recurrent respiratory infections in the DS population. Methods: A systematic literature review was conducted of published medical literature within the following databases: MEDLINE, Science Direct, and The Cochrane Library. A systematic search for ongoing clinical trials and guidelines/consensus statements was performed using various clinical trial registers and professional organisation websites. Search terms included 'DS', 'Trisomy 21', 'paediatric', 'respiratory infections', 'recurrent respiratory infections', 'prophylaxis' and 'antibiotics'. Systematic reviews, meta-analyses, randomised controlled trials, case-control studies and case-series were considered. Results: A systematic search revealed 0 published articles and 0 clinical trials meeting the necessary inclusion criteria. 1 guideline was found meeting our inclusion criteria; the Nottingham Guideline which outlines the role of prophylactic antibiotics in the DS population. Given the dearth of evidence in this area, we formulated a clinical trial to investigate the utility of prophylactic antibiotics for current respiratory infections in the DS population. Azithromycin was chosen as the antibiotic of choice for its anti-inflammatory and immunomodulatory properties. Primary endpoints would be the number of respiratory infections experienced over the course of the treatment period requiring a GP or ED attendance. Secondary endpoints include the severity of respiratory infections, both the number and severity of adverse events experienced over the period of the trial, along with the patient and parent/legal guardian self-reported quality of life. Conclusion: There is a current lack of evidence supporting or refuting the use of prophylactic antibiotics for recurrent respiratory infections in DS. Basic scientific studies need to be performed elucidating the role of anatomical and immunological features in predisposing children with DS to recurrent respiratory infections. Clinical trials are needed to elucidate whether prophylactic antibiotics are useful in this cohort and to investigate the optimal timing and combination of antibiotics. Guidelines are needed to support physicians in clinical decision making.